Wavelength Dependent Haze of Transparent Glass-Particle Filled Poly(Methyl Methacrylate) Composites. (12th March 2014) - Wildner, Wolfgang; Drummer, Dietmar
Abstract : Glass particles as filler were incorporated in a poly(methyl methacrylate) matrix. The refractive indexes of both materials match at a wavelength of about 400 nm. The effect of particle volume fraction on the light transmittance and light scattering (haze) in dependence of the refractive index difference was studied. The curve shape of the haze in dependence of the wavelength is comparable to that of the refractive index difference, but the base line of the haze increases with the filling grade. This indicates that there are other scattering or absorbing mechanisms, like defects in the filler binding.